2013
DOI: 10.1111/j.1600-6143.2012.04327.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Corticosteroid Withdrawal on Tacrolimus and Mycophenolate Mofetil Exposure in a Randomized Multicenter Study

Abstract: As corticosteroid-sparing protocols are increasingly utilized in kidney transplant recipients, it is crucial to understand potential drug interactions between tacrolimus (TAC) and the effect of corticosteroid withdrawal as well as to characterize dose adjustments of mycophenolate mofetil (MMF) in this setting. This prospective, multicenter, randomized, double-blind study included 397 patients who were randomized on posttransplant day 8 to receive either placebo (CSWD) or corticosteroid continuance (CCS). TAC t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
6
8
0
Order By: Relevance
“…It seems likely that these differences arise from variations in interstitial CYP 3A or P‐glycoprotein activities between ethnic groups . There is also robust evidence that concomitant steroid administration enhances tacrolimus clearance in a dose‐dependent manner , with an increase in dose‐adjusted tacrolimus exposure observed following steroid dose reduction or following steroid withdrawal . In our cohort, similarly, we observed markedly lower bioavailability of tacrolimus in African American recipients as well as in patients receiving steroids.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…It seems likely that these differences arise from variations in interstitial CYP 3A or P‐glycoprotein activities between ethnic groups . There is also robust evidence that concomitant steroid administration enhances tacrolimus clearance in a dose‐dependent manner , with an increase in dose‐adjusted tacrolimus exposure observed following steroid dose reduction or following steroid withdrawal . In our cohort, similarly, we observed markedly lower bioavailability of tacrolimus in African American recipients as well as in patients receiving steroids.…”
Section: Discussionsupporting
confidence: 60%
“…One analysis reported reduced tacrolimus bioavailability in diabetic transplant recipients , but elsewhere only a delayed time to peak concentration was observed, with no difference in AUC . Indeed, a recent trial demonstrated that kidney transplant recipients with pre‐transplant diabetes required lower mean tacrolimus doses to maintain similar trough concentrations to non‐diabetic patients . It is possible that gastroparesis, which occurs frequently in diabetic individuals , could delay tacrolimus absorption for a while.…”
Section: Discussionmentioning
confidence: 99%
“…The cytochrome P450 3A4 isoenzyme is the principal enzyme responsible for TAC metabolism in the liver , and this isoenzyme is also known to be induced by corticosteroids . Thus, an increased rate of TAC metabolism (thus, lower TAC blood levels) would be expected to occur in the presence of corticosteroid use, and our results along with some other reports appear to confirm this relationship.…”
Section: Discussionsupporting
confidence: 88%
“…The results of our multivariable analyses of TAC dose and trough levels among 578 adult primary kidney transplant recipients support the results of other studies in that the TAC dose administered during the first 36 months post‐transplant was significantly higher among African American and younger transplant recipients and also significantly higher during the first 12 months post‐transplant among patients who were receiving maintenance corticosteroids . None of the other baseline and demographic variables, including recipient gender, influenced the TAC dose.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation